Mathematical modeling of systemic colorometric parameters unmasking wild waterfowl - Balym Yuriі; Vуsotska Olena; Pecherska, Anna; Bespalov, Yurii (Eastern-European Journal of Enterprise Technologies, 2017)
The research presents results of modeling of systemic colorometric parameters, unmasking wild waterfowl. The problem of unmasking wild waterfowl is acquiring practical relevance in connection with problems of biosafety. Such problems are associated with hotbeds and ways of spreading of avian influenza and a number of other dangerous infections and infestations. Moreover, the study of regularities of formation of animals’ protective coloration is of interest in terms of a number of fundamental problems of biology and ecology. As a result of conducted research with the use of a new class of mathematical models (DMDS), the authors offered a formalized description of systemic aspects that distinguish between protective coloration of mallard ducks and colorometric parameters of plant communities. The idealized trajectory of the system, reflecting dynamics of colorometric parameters of phytocenosis in the habitat of mallard duck, was constructed. The idealized pseudo-trajectory of the system, reflecting a set of combinations of colorometric parameters of protective coloration of mallard duck, was constructed. The kind of systemic colorometric parameter, which allows unmasking the mallard duck against the background of phytocenosis, was determined. Root mean square deviation of values of difference of colorometric parameters of digital photography of the researched area was selected as the systemic colorometric parameter. The systemic colorometric parameter reflects variability of ratios of difference of values of colorometric parameters in the sample of microsegments, into which the segments of the image of the studied area are divided. The obtained results offer new approaches to development of remote methods of studying living conditions and migration routes of wild waterfowl.